Analisis Nilai CTDIvol Dan DLP Pada Pemeriksaan CT Scan Brain Non Kontras Dewasa Untuk Periode Januari – Desember 2022 Di Instalasi Radiologi Rumah Sakit X Jakarta Pusat - Pricilia Shalry Horuoby; Anak Agung Aris Diartama; I Kadek Sukadana (Pusat Riset dan Inovasi Nasional, 2023)
Background: CT scans are used for various types of examinations such as examinations of the head, thorax, abdomen and so on. The most frequently performed CT scan is a CT scan of the head. However, in the medical field, especially radiology, CT scans have the highest dose compared to other radiation equipment. Efforts to reduce radiation doses and radiation effects are by estimating the correct dose given to CT Scan patients using an optimization index called DRL (Diagnostic Level Reference), namely by evaluating the values ​​of CTDIvol and DLP on CT scans of the head, which have been determined in accordance with BAPETEN/I-DRL 2021 standards. Method: This research is a descriptive quantitative study with an observational approach which aims to analyze CTDIvol and DLP values ​​based on retrospective data on non-contrast brain CT scans at the Radiology Installation at Hospital X, Central Jakarta. Results: Calculation of the 2nd quartile (50th percentile) value of CTDIvol and DLP in Adult Non-Contrast Brain CT Scan examinations for the January-December 2022 Period at the Radiology Installation at X Hospital, Central Jakarta is CTDIvol 55.51 mGy and DLP 867.00 mGy* cm. Conclusion: The 50 percentile value of CTDIvol and DLP in the Adult Non-Contrast Brain CT Scan examination for the January-December 2022 period at the Radiology Installation at X Hospital, Central Jakarta is in accordance with the standards set by BAPETEN/I-DRL 2021. Where is the value for CT Non-Contrast Head Scan, namely a CTDIvol value of 60 mGy and a DLP value of 1275 mGy*cm.